The Relationship of Training to the Performance of Pagar Merbau District Education Office Staff - Irma Nurmala Sari (Enrichment : Journal of Management, 2018)
This study is entitled "The Relationship of Training on Employee Performance of the District Education Office in Pagar Merbau". The main objective of this study is to analyze the relationship between training and the performance of Pagar Merbau District Education Office employees. The research method used was a qualitative sample of this study as many as 136 people from 136 employees of the District Education Office Pagar Merbau. Data collection is done by distributing questionnaires. Field data are then processed using the SPSS 23 program. As well as t test analysis to prove the research hypothesis. The results showed that the training gave a positive relationship to the performance of Pagar Merbau District Education Office employees with tcount> ttable (10,482> 1,656), then H0 was rejected and Ha was accepted, a significant level using α = 5% (0.5) resulted from this study significant 0.00 means that the error rate is smaller than 0.5, meaning that the partial variable of training has a positive relationship with the performance of Pagar Merbau District Education Department employees.